A highly effective ferritin-based divalent nanoparticle vaccine shields Syrian hamsters against lethal Nipah virus - Yin, Chunhong; Yao, Yan Feng; Yang, Peipei; Liu, Hang; Gao, Ge; Peng, Yun; Chen, Miaoyu; Lu, Mingqing; Zhang, Xuekai; Guo, Weiwei; Zhang, Zihan; Hu, Xue; et al. (Frontiers in Immunology, 2024)
The Nipah virus (NiV), a highly deadly bat-borne paramyxovirus, poses a substantial threat due to recurrent outbreaks in specific regions, causing severe respiratory and neurological diseases with high morbidity. Two distinct strains, NiV-Malaysia (NiV-M) and NiV-Bangladesh (NiV-B), contribute to outbreaks in different geographical areas.Currently, there are no commercially licensed vaccines or drugs available for prevention or treatment. In response to this urgent need for protection against NiV and related henipaviruses infections, we developed a novel homotypic virus-like nanoparticle (VLP) vaccine co-displaying NiV attachment glycoproteins (G) from both strains, utilizing the self-assembling properties of ferritin protein. In comparison to the NiV G subunit vaccine, our nanoparticle vaccine elicited significantly higher levels of neutralizing antibodies and provided complete protection against a lethal challenge with NiV infection in Syrian hamsters. Remarkably, the nanoparticle vaccine stimulated the production of antibodies that exhibited superior cross-reactivity to homologous or heterologous henipavirus. These findings underscore the potential utility of ferritinbased nanoparticle vaccines in providing both broad-spectrum and long-term protection against NiV and emerging zoonotic henipaviruses challenges.